Transcript Polymorphism Rates in Soybean Seed Tissue Are Increased in a Single Transformant of Glycine max. (29th November 2016) - Lambirth, Kevin C.; Whaley, Adam M.; Schlueter, Jessica A.; Piller, Kenneth J.; Bost, Kenneth L.
Abstract : Transgenic crops have been utilized for decades to enhance agriculture and more recently have been applied as bioreactors for manufacturing pharmaceuticals. Recently, we investigated the gene expression profiles of several in-house transgenic soybean events, finding one transformant group to be consistently different from our controls. In the present study, we examined polymorphisms and sequence variations in the exomes of the same transgenic soybean events. We found that the previously dissimilar soybean line also exhibited markedly increased levels of polymorphisms within mRNA transcripts from seed tissue, many of which are classified as gene expression modifiers. The results from this work will direct future investigations to examine novel SNPs controlling traits of great interest for breeding and improving transgenic soybean crops. Further, this study marks the first work to investigate SNP rates in transgenic soybean seed tissues and demonstrates that while transgenesis may induce abundant unanticipated changes in gene expression and nucleotide variation, phenotypes and overall health of the plants examined remained unaltered.